Rozpoznawanie rodzaju heteroskedastyczności składników losowych modelu ekonometrycznego z wykorzystaniem dyskryminacyjnej reguły największej wiarygodności - Grześkowiak, Alicja (Recognition of the Heteroscedasticiy Type of Disturbances of the Econometric Model by Applying the Maximum Likelihood Discriminant Rule, 2007)
This paper presents a method of determination of the heteroscedasticity type in the linear econometric model. The postulated concept combines advantages of the non-constructive test with the usage of the maximum likelihood discriminant rule. The suggested solution is illustrated by models describing the dependence of expenses and income.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (14); 2007; nr 1169, s. 482-488